NAMD goes quantum: an integrative suite for hybrid simulations - Melo, Marcelo C. R.; Bernardi, Rafael C.; Rudack, Till; Scheurer, Maximilian; Riplinger, Christoph; Phillips, James C.; Maia, Julio D. C.; Rocha, Gerd B.; Ribeiro, João V.; Stone, John E.; Neese, Frank; Schulten, Klaus; et al. (Nature methods, 2018)
The integration of quantum chemistry and molecular dynamics programs coupled with a graphical user interface provides a streamlined tool for powerful simulations of biomolecular reaction mechanisms.
Gesehen am 26.03.2020